Antiangiogenic ruthenium(ii) benzimidazole complexes, structure-based activation of distinct signaling pathways1. Issue 3 (11th March 2015) - Lai, Haoqiang; Zhao, Zhennan; Li, Linlin; Zheng, Wenjie; Chen, Tianfeng
<x xml:space="preserve">Abstract</x> A series of ruthenium(ii) benzimidazole complexes has been synthesized and identified as antiangiogenic agents with distinct structure-based action mechanisms.